ANALYSIS OF THE COMPETITIVENESS OF THE SHARIA INSURANCE SECTOR IN FACING THE CHALLENGE OF SOCIETAL INTEGRATION IN INDONESIA - Sari Harahap, Siska Permata; Daulay, Aqwa Naser; Budi Harianto (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the competitiveness of the sharia insurance sector in Indonesia in facing the challenges of community integration. The research method used is a qualitative descriptive approach through in-depth interviews with academics and practitioners in the field of sharia insurance. The results of the study indicate that this sector has great potential supported by the majority of the Muslim population, but still faces serious challenges such as low insurance penetration and literacy, limited product innovation, and less than optimal use of digital technology. To increase competitiveness, strategies that need to be implemented include sharia financial literacy education, digitalization of services based on sharia principles, development of products that are relevant to community needs, and collaboration with various stakeholders. This study emphasizes the importance of the role of regulation, innovation, and cross-sector integration to strengthen the competitiveness of sharia insurance in the era of community economic integration.